Polymorphism of the Androgen Receptor Gene is Associated with Male Pattern Baldness - Ellis, Justine A.; Stebbing, Margaret; Harrap, Stephen B. (Journal of investigative dermatology, 2001)
The common heritable loss of scalp hair known as male pattern baldness or androgenetic alopecia affects up to 80% of males by age 80. A balding scalp is characterized by high levels of the potent androgen dihydrotestosterone and increased expression of the androgen receptor gene. To determine if the androgen receptor gene is associated with male pattern baldness, we compared allele frequencies of the androgen receptor gene polymorphisms (StuI restriction fragment length polymorphism and two triplet repeat polymorphisms) in cases with cosmetically significant baldness (54 young and 392 older men) and controls (107 older men) with no indication of baldness. The androgen receptor gene StuI restriction site was found in all but one (98.1%) of the 54 young bald men (p =0.0005) and in 92.3% of older balding men (p =0.000004) but in only 76.6% of nonbald men. The combination of shorter CAG and GGC triplet repeat lengths was also more prevalent in bald men (p =0.03). The ubiquity of the androgen receptor gene StuI restriction site, and higher incidence of shorter triplet repeat haplotypes in bald men suggests that these markers are very close to a functional variant that is a necessary component of the polygenic determination of male pattern baldness. Functional mutation in or near the androgen receptor gene may explain the reported high levels of expression of this gene in the balding scalp.